New materials for solar cells - Tan, Kah Heng. (2009)
This project report documents on the chemical synthesis and characterization of organic compounds to ascertain its use as electron donor materials in hybrid organic-inorganic solar cells. The chemical synthesis entails the Knoevenagel condensation reactions between the compounds; 3,6-diformyl-9-n-dodeylcarbazole and several other differently substituted acetonitrile derivatives. These compounds are as follows; 3,4-dimethoxy-phenylacetonitrile, 4-methoxy-phenylacetonitrile, 5-methoxy3iodo-phenylacetonitrile and 2-thiopheneacetonitrile. All the final compounds obtained were characterized by nuclear magnetic resonance (NMR) spectroscopy, fluorescence spectroscopy and also Ultraviolet- Visible (UV-Vis) spectroscopy. The band gap energy and respective absorbance wavelength can be estimated from the UV-Vis spectra. This will help to identify the criteria for successful application of the obtained materials for the purpose of hybrid solar cells, and enable the predicting of how various substituted functional groups has effects on the regions or peaks of absorption. This will aid in molecular design which entails creating better materials to match CdSe nanoparticles so as to maximize absorbance from the solar spectrum as much as possible in a complementary manner. From the NMR spectroscopy, promising results are present, suggesting that compound 11 has been obtained through the chemical reaction. Besides, the use of UV-Vis spectroscopy has also enabled deductions with regards to the effects of various functional groups on the absorbance and band gap energies. In general, the presence of electron-withdrawing groups tend to redshift the absorbance wavelength of the material and reduce the band gap energy as seen in compound 12 which has the most withdrawing groups (i.e. meta methoxy and Iodo) while the opposite holds true for electron-donating functional groups as seen in compound 10 (i.e. Para methoxy).